2013
DOI: 10.1016/j.physa.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analogy between economical crisis and earthquake dynamics within the nonextensive statistical mechanics framework

Abstract: The field of study of complex systems considers that the dynamics of complex systems are founded on universal principles that may be used to describe a great variety of scientific and technological approaches of different types of natural, artificial, and social systems. Several authors have suggested that earthquake dynamics and the dynamics of economic (financial) systems can be analyzed within similar mathematical frameworks. We apply concepts of the nonextensive statistical physics, on time-series data of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…In particular, lower S q TS values characterize portions of the signal with lower complexity [46]. In this article, for the calculation of Tsallis entropy, we have chosen to use the value q TS = 1.8 for the non-extensive parameter, q TS , after [20,51].…”
Section: Tsallis Entropymentioning
confidence: 99%
“…In particular, lower S q TS values characterize portions of the signal with lower complexity [46]. In this article, for the calculation of Tsallis entropy, we have chosen to use the value q TS = 1.8 for the non-extensive parameter, q TS , after [20,51].…”
Section: Tsallis Entropymentioning
confidence: 99%
“…In the case of noisy time series, the value of q is often selected such that the signal is better discriminated from the noise and this value of the entropic index is considered to be related to the (multi)fractal structure of the signal(s) under study, which in turn reflects the deep microscopic or mesoscopic (generically non-linear) dynamics in the phase space of the underlying system (Tsallis, 1998). However, if possible, the appropriate value of q should be selected by other independent means, like the best fit to models or distributions expressing the dynamics of the underlying system (Tsallis and de Albuquerque, 2000;Minadakis et al, 2012a,b;Potirakis et al, 2013;Vallianatos, 2013;Efstathiou et al, 2016;Michas et al, 2016).…”
Section: Non-extensive Tsallis Entropymentioning
confidence: 99%
“…The relatively new field of complex systems increasingly gains the interest of scientists working on disciplines ranging from physics and engineering to economics, biosciences, and social sciences, e.g., [1][2][3][4][5][6][7][8]. The unique characteristic of complex systems is that they may have certain quantitative features that are intriguingly similar, while their dynamics are governed by a set of universal principles [9,10]. Thus, complex systems from different disciplines are often analyzed within similar mathematical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…A number of analysis methods have been mutually used to study the dynamics of financial markets, earthquakes, and magnetosphere, e.g., [17,[32][33][34][35][38][39][40][41][42][43][44][45][46][47][48][49][50]. Several authors have suggested that earthquake dynamics and the dynamics of economic (financial) systems can be analyzed within similar mathematical frameworks, e.g., [10] and references therein [14,[51][52][53][54]. On the other hand, authors have also suggested that earthquake dynamics and MSs dynamics can be analyzed within similar mathematical frameworks, as well, e.g., [33][34][35].…”
Section: Introductionmentioning
confidence: 99%